Noninvasive prenatal diagnosis for pregnancies at risk for β‐thalassaemia: a retrospective study. (28th May 2020) - Lv, W; Linpeng, S; Li, Z; Liang, D; Jia, Z; Meng, D; Cram, DS; Zhu, H; Teng, Y; Yin, A; Wu, L
Abstract : Objective: To evaluate the clinical feasibility of noninvasive prenatal diagnosis (NIPD) for β‐thalassaemia using circulating single molecule amplification and re‐sequencing technology (cSMART). Design: Through carrier screening, 102 pregnant Chinese couples carrying pathogenic HBB gene variants were recruited to the study. Pregnancies were managed using traditional invasive prenatal diagnosis (IPD). Retrospectively, we evaluated the archived pregnancy plasma DNA by NIPD to evaluate the performance of our cSMART assay for fetal genotyping. Setting: Chinese prenatal diagnostic centres specialising in thalassaemia testing. Population: Chinese carrier couples at high genetic risk for β‐thalassaemia. Methods: Fetal cell sampling was performed by amniocentesis and HBB genotypes were determined by reverse dot blot. NIPD was performed by a newly designed HBB cSMART assay and fetal genotypes were called by measuring the allelic ratios in the maternal cell‐free DNA. Main outcome measures: Concordance of HBB fetal genotyping between IPD and NIPD and the sensitivity and specificity of NIPD. Results: Invasive prenatal diagnosis identified 29 affected homozygotes or compound heterozygotes, 54 heterozygotes and 19 normal homozygotes. Compared with IPD results, 99 of 102 fetuses (97%) were correctly genotyped by our NIPD assay. Two of three discordant samples were false positives and the other sample involved an incorrect call of a heterozygote carrier as a homozygote normal. Overall, the sensitivity and specificity of our NIPD assay was 100% (95% CI 88.06–100.00%) and 97.26% (95% CI 90.45–99.67%), respectively. Conclusions: This study demonstrates that our cSMART‐based NIPD assay for β‐thalassaemia has potential clinical utility as an alternative to IPD for pregnant HBB carrier couples. Tweetable abstract: A new noninvasive test for pregnancies at risk for β‐thalassaemia. Tweetable abstract: A new noninvasive test for pregnancies at risk for β‐thalassaemia.